Communion, purpose of cultural-missionary communication in the media - Tănăsescu, Eugen (Technium Social Sciences Journal, 2023)
Communion deeply defines the cultural-spiritual values of the Church; therefore, it is an essential goal of cultural-missionary communication. When it is carried out through the media, communication generates the appearance of a relationship between three components: broadcast-mission-communion, which has a double role in society: on the one hand it affirms the cultural-spiritual values of the Church, on the other hand it is a counterweight to contemporary cultural-spiritual degradation through media pollution. This study aims to analyze the relationship between the three mentioned components as well as the double role they have in society.